CO2 and N2O flux balance on soybean fields during growth and fallow periods in the Argentine Pampas—A study case - Lewczuk, Nuria Andrea (2017)
The estimation of the GHG balance of agroecosystems is essential to evaluate the impact of agriculture on the composition of the atmosphere. Cultivated soils may act as a sink or a source of CO2 and usually emit N2O. The aim of the present study was to assess the CO2 and N2O balances, and to analyze the relationships between N2O fluxes and environmental variables for two soybean growing seasons and the fallow period between them, in an agricultural field in the Pampas region of Argentina. The fluxes of CO2 and N2O were measured by the eddy covariance and the static-chamber methods, respectively. The net ecosystem exchange from sowing to harvest was −2543 and −2307 kg CO2-C ha−1, for the first and second growing seasons, respectively. The N2O net balance over the same periods was 1.45 and 0.96 kg N2O-N ha−1. A multivariate analysis showed that during the growing season the most important variable influencing N2O emission was % water filled pore space (% WFPS), followed by nitrate content and soil temperature. During fallow, soil temperature was the main control factor, followed by % WPFS. The total balance (including CO2 and N2O) showed that the soil gained 753.5 kg Ceq ha−1 on average during cultivarion cycle. Taking into account the fallow period, the global balance resulted in a carbon loss of 1328.5 kg Ceq ha−1 over about one year. Our results clearly indicate the need to incorporate winter cover crops for improving the production system, as they can provide carbon to the soil and use the available stubble nitrogen from the previous crop.